NURSES' CARING BEHAVIORS IN THE IMPLEMENTATION OF PERIOPERATIVE NURSING CARE IN PUBLIC HOSPITALS OF BAHTERAMAS KENDARI - Heltty Heltty (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. Caring is the main focus in the field of nursing. Caring relate to the quality of nursing care. Public demand to the quality of nursing care is increasing. The purpose of this study was to analyze the nurses’ caring behavior in the implementation of perioperative nursing care in public hospitals of Bahteramas Kendari. Methode. This research was qualitative research: naturalistic. Participant selection method used was purposive sampling as many as six participants (nurses). The data obtained through observation using the observation guide in the form of a nurse caring behavior assessment instrument that Thai Nurses' Caring Behavior (TNCB). Qualitative data analysis was done interactively and lasted continuously until complete, so that the data was saturated. Result. Results of the study showed that participants described caring behavior quite well, although not all aspects of the nurse caring behaviors can be done. Discussion. Increasing in knowledge and skills nurses need to be done in an effort to develop caring in the practice of nursing services included in perioperative nursing care.Keywords: Caring, Nurse, Perioperative Nursing Care